Cultural Caste Systems in Indonesia: Continuity, Transformation, and Their Implications in Modern Society - Maimunah Ritonga (JISOSEPOL: Jurnal Ilmu Sosial Ekonomi dan Politik, 2026)
This study examines the continuity, transformation, and contemporary implications of cultural caste systems among indigenous communities in Labuhanbatu Regency, North Sumatra, Indonesia. Although Indonesia does not formally recognize hereditary caste systems, localized forms of social hierarchy rooted in adat (customary law), genealogy, and traditional leadership continue to influence social relations. The research aims to analyze the historical continuity of these cultural hierarchies, identify their transformation in the domains of education, marriage, politics, and the economy, and assess their implications for social identity, inequality, and community cohesion. Employing a qualitative research design with historical and ethnographic approaches, the study collected data through in-depth interviews, focus group discussions, participant observation, and document analysis involving customary leaders, community elders, youth, and local political actors. The findings reveal that hereditary status and adat authority remain important sources of symbolic legitimacy, particularly in customary ceremonies, conflict resolution, and community leadership. However, modernization, democratization, and globalization have significantly transformed the basis of social status, with educational attainment, professional achievement, economic success, and political participation increasingly complementing or replacing hereditary privilege. Rather than disappearing, cultural caste systems have adapted to contemporary conditions by functioning as flexible symbolic institutions that preserve indigenous identity while accommodating social change. Furthermore, these systems contribute to both social cohesion and inequality by reinforcing customary solidarity while maintaining differential access to social networks and local authority. The study concludes that the cultural caste system in Labuhanbatu represents a dynamic institution that continues to shape identity, social mobility, and governance in modern Indonesia, highlighting the need for policies that balance cultural preservation with the promotion of equality and inclusive development.